2021
DOI: 10.3389/fimmu.2021.677848
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Affect IL-33 Processing in Response to the Respiratory Allergen Alternaria alternata

Abstract: Future precision medicine requires further clarifying the mechanisms of inflammation in the severe endotypes of chronic airway diseases such as asthma and chronic rhinosinusitis (CRS). The presence of neutrophils in the airways is often associated with severe airway inflammation, while their precise contribution to the severe inflammation is largely unknown. We aimed to study the role of neutrophils in BALB/c and C57BL/6 mice exposed to Alternaria alternata (Alt). The mice were exposed to Alt extract for twelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
(59 reference statements)
3
11
0
Order By: Relevance
“…Histologically, lung tissue appeared more inflamed in Alternaria -treated Rora Cre+ Chat LoxP and Chat LoxP mice relative to untreated controls ( Figure 1D ). In the airways, alveolar macrophages (AM) were the dominant cell type in WT control mice, whereas significantly increased eosinophils and neutrophils were observed in Alternaria exposed Rora Cre+ Chat LoxP and Chat LoxP genotypes ( Supplemental Figure 1 and Figures 1E, F ) as expected ( 14 , 17 ). Airway eosinophil numbers were comparable between Alternaria -exposed genotypes ( Figure 1E ), but more neutrophils were observed in Rora Cre+ Chat LoxP mice ( Figure 1F ), indicating a role for ILC2-derived ACh in regulating neutrophil influx following exposure to Alternaria .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Histologically, lung tissue appeared more inflamed in Alternaria -treated Rora Cre+ Chat LoxP and Chat LoxP mice relative to untreated controls ( Figure 1D ). In the airways, alveolar macrophages (AM) were the dominant cell type in WT control mice, whereas significantly increased eosinophils and neutrophils were observed in Alternaria exposed Rora Cre+ Chat LoxP and Chat LoxP genotypes ( Supplemental Figure 1 and Figures 1E, F ) as expected ( 14 , 17 ). Airway eosinophil numbers were comparable between Alternaria -exposed genotypes ( Figure 1E ), but more neutrophils were observed in Rora Cre+ Chat LoxP mice ( Figure 1F ), indicating a role for ILC2-derived ACh in regulating neutrophil influx following exposure to Alternaria .…”
Section: Resultssupporting
confidence: 61%
“…Given our observations in Rora Cre+ Chat LoxP mice, we were particularly interested in examining the neutrophilic response following ACh depletion. Therefore, we used BALB/c mice, which have a dominant early neutrophilic response to Alternaria exposure compared with C57BL/6 mice, which are more eosinophil-dominant ( 17 ). The enzymes were co-administered intranasally with Alternaria , as shown in Supplemental Figure 4A .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, both full-length and cleaved forms of IL-33 could be detected in bronchoalveolar lavage fluid in an in vivo model of acute lung injury associated with neutrophil infiltration [ 16 ]. Later, these results have been confirmed by at least two other papers, in vitro [ 170 ] and in vivo [ 171 ]. Similarly, several studies have shown that PR3 converts inactive human and murine IL-33 precursor proteins into biologically active forms [ 16 , 172 ] before abrogating IL-33 activities, when increasing PR3 incubation time or using excessive protease concentration [ 170 , 172 ].…”
Section: Regulation Of Il-33supporting
confidence: 61%
“…We previously identified granulocyte colony-stimulating factor (G-CSF) as a cytokine that is selectively upregulated in neutrophilia-prone BALB/c mice but not in eosinophilia-prone C57BL/6 mice subjected to an Alternaria alternata-induced mouse model of allergic inflammation. 13 G-CSF is a cytokine produced by bone marrow stromal cells, macrophages, fibroblasts, epithelial and endothelial cells, in response to a bacterial or viral infection. 14 Its functions include stimulation of the proliferation and differentiation of neutrophils from progenitors in the bone marrow and promotion of their recruitment into tissues.…”
Section: Introductionmentioning
confidence: 99%